A selective colorimetric chemosensor for detection of Cu(II) ions in aqueous samples - Ferretti, Cristián Alejandro; Gutierrez, Leandro Gabriel; Guntero, Vanina Alejandra; Noriega, Pablo Javier; Kneeteman, María Nelida (Comptes Rendus. Chimie)
In this work we report a selective colorimetric chemosensor (S) for $Cu^{2+}$ ion detection in aqueous media. It has been synthesized by a condensation reaction between 1-hydrazinophtalazine and 6,$6^{′}$-dihydroxy-5,$5^{′}$dimethoxy-(1,$1^{′}$-biphenyl)-3,$3^{′}$-dicarbaldehyde. The interaction between S and $Cu^{2+}$ was studied and the results showed a bathochromic shift at 420 nm in UV–Vis spectra. The absorbance enhancement of S was attributed to complex formation with $Cu^{2+}$ by 2:1 stoichiometry. The proposed analytical method can be applied to $Cu^{2+}$ quantification with a linear range covering from 5.0 to $315.8~{μ }$M, and can be used to routinely analyze $Cu^{2+}$ in environmental aqueous samples with satisfactory results.